2017
DOI: 10.26444/aaem/80699
|View full text |Cite
|
Sign up to set email alerts
|

Design, construction and evaluation of multi-epitope antigens for diagnosis of Lyme disease

Abstract: Introduction and objective. Lyme disease (LD) is the most common vector-borne disease in the temperate zone of the Northern Hemisphere. Diagnosis of LD is mainly based on clinical symptoms supported with serology (detection of antiBorrelia antibodies) and is often misdiagnosed in areas of endemicity. Materials and method. In this study, the chimeric proteins (A/C-2, A/C-4 and A/C-7.1) consisting of B-cell epitopes of outer surface proteins OspA and OspC from Borrelia genospecies prevalent in Eastern Slovakia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Successful application of chimeric proteins, assembled using molecular biology techniques, in immunological assays for the diagnosis of viral, bacterial and parasitic diseases has already been demonstrated (Alcaro et al, 2003;Holec-Gąsior et al, 2012a, Holec-Gąsior et al, 2012bDrapała et al, 2014;Ferra et al, 2015). To date, only a few studies have shown the reactivity of this kind of proteins with specific IgG antibodies from human sera of individuals with Lyme borreliosis (Gomes-Solecki et al, 2000;Schreterova et al, 2017). However, chimeric proteins are a new generation of recombinant products which have the potential to replace the native antigen (e.i.…”
Section: Resultsmentioning
confidence: 99%
“…Successful application of chimeric proteins, assembled using molecular biology techniques, in immunological assays for the diagnosis of viral, bacterial and parasitic diseases has already been demonstrated (Alcaro et al, 2003;Holec-Gąsior et al, 2012a, Holec-Gąsior et al, 2012bDrapała et al, 2014;Ferra et al, 2015). To date, only a few studies have shown the reactivity of this kind of proteins with specific IgG antibodies from human sera of individuals with Lyme borreliosis (Gomes-Solecki et al, 2000;Schreterova et al, 2017). However, chimeric proteins are a new generation of recombinant products which have the potential to replace the native antigen (e.i.…”
Section: Resultsmentioning
confidence: 99%
“… Recombinant protein E. coli BL21(DE3) cells Indirect ELISA 146 brucellosis-positive serum samples/20 serum samples from healthy individuals/82 serum samples from non-brucellosis diseases Sensitivity: 88.89% Specificity: 85.54% [ 44 ]/China Human Lyme disease/ Borrelia burgdorferi A/C-2, A/C-4, and A/C-7.1 E . coli (XL1-Blue) cells ELISA 169 Lyme-positive serum samples/5 serum samples from healthy individuals A/C-2 Sensitivity: 80.17% Specificity: 52.83% A/C-4 results not shown A/C-7.1 Sensitivity: 91.37% Specificity: 73.58% [ 45 ]/Slovakia Human and goat brucellosis/ Brucella spp. rOmp E. coli BL21(DE3) cells Indirect ELISA 40 human and 31 goat brucellosis-positive serum samples/20 healthy human and 20 healthy goat serum samples rOmp was recognized by human and goat positive samples [ 46 ]/China Goat brucellosis/ Brucella spp.…”
Section: Rmps Applied In Disease Diagnosismentioning
confidence: 99%
“…Schreterova et al (2017) [ 45 ] conducted a study aimed at developing new RMPs for diagnosing Lyme disease, caused by Borrelia burgdorferi . After using phage display and multiple alignments for epitope selection, the new RMPs, named A/C-2, A/C-,4, and A/C-7.1, were expressed in E .…”
Section: Rmps Applied In Disease Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Epitope characterization can also help elucidate the mechanism of antibody binding (Davidson et al 2015 ) and can enforce intellectual property (patent) protection for the novel antibodies (Deng et al 2018 ; Ledford 2018 ). Experimental epitope mapping data can be incorporated into robust algorithms to facilitate the in silico prediction of B-cell epitopes based on sequence and/or structural data (Schreterova et al 2017 ; Leclair and Lim 2020 ). Epitopes are generally divided into two classes: linear and conformational.…”
Section: Introductionmentioning
confidence: 99%